State of forage base for pacific salmons in the Bering Sea in 2003-2012 (by results of surveys of the international expeditions BASIS-1 and 2) - Anatoly F. Volkov (Известия ТИНРО, 2014)
The BASIS expeditions in the Bering Sea were conducted by North Pacific Anadromous Fish Comission (NPAFC) in the 2003-2006 and 2007-2012, in relatively warm and relatively cold conditions, respectively. The ice cover of the Sea changed synchronously in its western and eastern parts and indicated the warm regime since 2001 to 2006 and the cold regime since 2006 till nowadays. The regime shift changed radically the structure of zooplankton community in the eastern Bering Sea: the dominance of small-sized and medium-sized zooplankton was replaced by the dominance of large-sized zooplankton, with abundant large species of euphausiids, hyperiids, copepods, and arrowworms. This restructuring was reflected in the diet of pacific salmon: the bulk of the pink, chum and sockeye salmons diet was presented by fingerlings of pollock, sand lance, and capelin, larvae of flounders and crabs, and fry of small demersal fish in 2003-2006, but by zooplankton as euphausiids, hyperiids, and pteropods since 2007. However, there weren’t so essential changes in the western Bering Sea, both in zooplankton structure and salmons diet; the year-to-year dynamics was significant here, too, but long-term tendencies were not observed.